Transcriptional profiling of synovium in a porcine model of early post‐traumatic osteoarthritis. Issue 8 (20th April 2018) - Sieker, Jakob T.; Proffen, Benedikt L.; Waller, Kimberly A.; Chin, Kaitlyn E.; Karamchedu, Naga Padmini; Akelman, Matthew R.; Perrone, Gabriel S.; Kiapour, Ata M.; Konrad, Johannes; Fleming, Braden C.; Murray, Martha M.
ABSTRACT: To determine the transcriptional profile of synovium during the molecular phase of post‐traumatic osteoarthritis, anterior cruciate ligament transections (ACL) were performed in 36 Yucatan minipigs. Equal numbers were randomly assigned to no further treatment, ACL reconstruction or repair. Perimeniscal synovium for histopathology and RNA‐sequencing was harvested at 1 and 4 weeks post‐operatively and from six healthy control animals. Microscopic synovitis scores significantly worsened at 1 ( p < 0.001) and 4 weeks ( p = 0.003) post‐surgery relative to controls, and were driven by intimal hyperplasia and increased stromal cellularity without inflammatory infiltrates. Synovitis scores were similar between no treatment, reconstruction, and repair groups ( p ≥ 0.668). Relative to no treatment at 1 week, 88 and 367 genes were differentially expressed in the reconstruction and repair groups, respectively (227 and 277 at 4 weeks). Relative to controls and with the treatment groups pooled, 1, 683 transcripts were concordantly differentially expressed throughout the post‐surgery time‐course. Affected pathways included, proteolysis_connective tissue degradation (including upregulations of protease‐encoding MMP1, MMP13, and ADAMTS4 ), and development_cartilage development (including upregulations of ACAN, SOX9, and RUNX2 ), among others. Using linear regression, significant associations of post‐surgery synovial expression levels of 20 genes with the articular cartilage glycosaminoglycan loss were identified. These genes were predominantly related to embryonic skeletal system development and included RUNX2 . In conclusion, this study confirmed an increased synovial expression of genes that may serve as targets to prevent cartilage degradation, including MMP1, MMP13, and ADAMTS4, in knees with microscopic synovitis and cartilage proteoglycan loss. Attractive novel targets include regulators of embryonic developmental processes in synovium. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2128–2139, 2018.